Profile of Leprosy Among Children in Jayapura City - Sumolang, Inneke V.; Indah, Astrina Rosaria; Reba, Timothy V. P (PT Inovasi Pratama Internasional, 2023)
Leprosy is a chronic infectious disease caused by Mycobacterium leprae with highly variable clinical presentations. Leprosy remains a health problem in Indonesia. Leprosy cases in children are an epidemiological index to determine disease transmission as an indicator of the success of the national leprosy eradication program. Objective: To analyze the picture of leprosy in children in Jayapura City. A retrospective study method was used to examine all new leprosy cases in children (0-14 years) in all community health centers in Jayapura City who came to the Community Health Center Outpatient Unit from January 2019 to December 2022. The results of this study revealed that of the 967 new leprosy cases, 811 (83.87%) were adults and 156 (16.13%) were children aged 0-14. The most common age group was 10-14 years with 96 people (61.54%). Male gender was 82 people (52.56%) and female gender was 74 people (47.44%). In general, there were 103 Papuans (66.03%), while 53 non-Papuans (33.97%) had multibacillary leprosy. 128 (82.05%) had paucibacillary leprosy, and 28 (17.95%) had paucibacillary leprosy. Twenty-three (14.75%) of the children with leprosy dropped out. The leprosy rate among children in Jayapura City remains very high, at around 16.13%.